Poor Motor Performance – Do Peers Matter? Examining the Role of Peer Relations in the Context of the Environmental Stress Hypothesis - Gasser-Haas, Olivia; Sticca, Fabio; Wustmann Seiler, Corina (Frontiers in Psychology, 2020)
The aim of the current study was to investigate important pathways of the Environmental Stress Hypothesis concerning the role of peer relations. First, we examined (1) the mediating role of peer problems in the association between the motor performance in daily activities and internalizing problems as a main pathway of the Environmental Stress Hypothesis. Furthermore, we explored the role of (2) children’s popularity as a mediator and (3) best friendship quality as a moderator path of the effect of motor performance on both peer problems and internalizing problems. The non-clinical sample of the present study consisted of 189 children (48.6% females) aged nine to eleven years (Mage = 9.69, SDage = 0.46). Parents reported on their child’s motor performance in daily activities by completing the Developmental Coordination Disorder Questionnaire. In addition, the Strengths and Difficulties Questionnaire was used to assess peer problems as well as internalizing problems. The Self Description Questionnaire provided a measure of children’s self-reported popularity. Finally, the Friendship Quality Questionnaire was used to investigate children’s best friendship quality. Results of a structural equation model suggest that peer problems fully mediated the association between the motor performance in daily activities and both popularity and internalizing problems. However, no evidence for the mediating effect of popularity in the association between peer problems and internalizing problems was found. Further, best friendship quality had small but non-significant positive moderating effect on the relation between peer problems and internalizing problems. The mediating role of peer problems highlights the importance of peer relations in the motor performance of daily activities. Possible reasons for the lack of some of the expected mediating and moderating effects as well as practical implications are discussed.